Preferential Neuronal Responses to Snakes in the Monkey Medial Prefrontal Cortex Support an Evolutionary Origin for Ophidiophobia - Dinh, Ha Trong; Nishimaru, Hiroshi; Le, Quan Van; Matsumoto, Jumpei; Setogawa, Tsuyoshi; Maior, Rafael S.; Tomaz, Carlos; Ono, Taketoshi; Nishijo, Hisao (Frontiers in Behavioral Neuroscience, 2021)
Ophidiophobia (snake phobia) is one of the most common specific phobias. It has been proposed that specific phobia may have evolutionary origin, and that attentional bias to specific items may promote onset of phobia. Noninvasive imaging studies of patients with specific phobia reported that the medial prefrontal cortex (mPFC), especially the rostral part of the anterior cingulate cortex (rACC), and amygdala are activated during presentation of phobogenic stimuli. We propose that the mPFC-amygdala circuit may be involved in pathogenesis of phobia. The mPFC receives inputs from the phylogenically old subcortical visual pathway including the superior colliculus, pulvinar and amygdala, while mPFC neurons are highly sensitive to snakes that are the first modern predator of primates, and discriminate snakes with striking postures from those with non-striking postures. Furthermore, the mPFC has been implicated in attentional allocation, and promotes amygdala-dependent aversive conditioning. These findings suggest that the rACC focuses attention on snakes, and promotes aversive conditioning to snakes, which may lead to anxiety and ophidiophobia.